Comparison of Carbon Dioxide Laser With Surgical Blade for Removal of Epulis Fissuratum. A Randomized Clinical Trial - karimi, Abbas; Sobouti, Farhad; Torabi, Sara; Bakhshandehfard, Ali; Amirian, Armaghan; Shariati, Mahsa; Morshedi, Ehsan; Barati, Maryam (Journal of Lasers in Medical Sciences, 2016)
Introduction: Epulis fissuratum is often formed as a result of a poor fitting denture. The conventional treatment for this fibrous hyperplastic tissue is to excise it using a scalpel and to close the wound by a continuous or an interrupted suture. The increased utilization of lasers in dentistry also includes the utilization of carbon dioxide (CO2) lasers in place of surgical scalpels in soft tissue surgeries. The objective of this study is to assess the feasibility of utilizing CO2 laser in place of scalpel in surgical treatment of epulis fissuratum. Methods:In this clinical trial research (IRCT code: IRCT2016071124969N2), 19 patients were selected with nearly symmetrical epulis fissuratums in the anterior part of the jaws. The hyperplastic tissue was evenly divided into two sections in each patient. One section was randomly selected and cut by CO2 laser and the other section by a surgical scalpel. The wound created by the scalpel was closed by appropriate number of interrupted sutures. Surgery duration and bleeding as well as vestibular depth, re-epithelialization and edema in both sections were noted and recorded after 7 and 14 days postoperatively. Results:The time of surgery and the amount of bleeding during surgery in the laser section was less and the vestibular depth was more than surgical scalpel section (P < 0.05). Surgical scalpel wound at day seventh healed significantly better than the section treated by the CO2 laser (P< 0.05). Wound in both sections healed similarly on day 14 and no statistical difference was observed. Edema presence was also equal in both sides after 7th and 14th following the surgery. Conclusion:According to the results it could be concluded that the use of CO2 laser may result in less surgery time, less bleeding during surgery, more vestibular depth, better re-epithelialization of the wound and less need for suturing. CO2 laser may be a clinically preferred method for surgical treatment of epulis fissuratum.